FEATURES OF IRON METABOLISM IN PATIENTS WITH ANEMIC SYNDROME WITH RHEUMATOID ARTHRITIS - Галина Северьевна Суржикова; Сатеник Аршавиловна Клочкова-Абельянц (Медицина в Кузбассе, 2025)
Objective – to study the features of iron metabolism and the pathogenetic mechanisms of anemia development in rheumatoid arthritis.